Presence of parasite larvae in goat faeces for use as fertiliser - Basripuzi Nurul Hayyan Hassan Basri; Sani, R.A; Ariff, O.M.; Chandrawathani, P. (2013)
The presence of strongyle larvae in goat manure needs to be determined as some farmers recycle the manure to fertilise grasses grown for animal feed which may lead to strongylosis. Five plots of at least 1.5 m apart were identified in grassy area. Faeces of goats with strongly infection diposited over a 24-hour period were collected and deposited onto the plots. Faecal samples were collected daily in the morning from each plot until eggs and strongyle larvae were no longer detected. The samples were subjected tp faecal egg count (FEC), larvae identification and enumeration. The mean FEC of samples declined from 660 eggs per gram (epg) on Day 1 to zero epg on Day 4. Pre-infective larvae were found on Days 4 and 5. L3 of Haemonchus contortus and Trichostrongylus sp. L3 were observed until Day 21 and Day 22 respectively. Oesophagostomum sp. L3 were absent by Day 16.Overall L3 counts peaked on day 8 and were negligible by Day 14. Thus, it is recommended that the manure heap be kept without continuous accumulation of fresh faeces for at least 14 Days before being applied as fertiliser.